A Weberian Analysis of the Perspectives of Individuals with a Migrant Background Regarding Joining Military Service in Finland - Bontenbal, Ilona; Riikonen, Reetta; Kosonen, Jarkko (Sosiologia, 2025)
This paper investigates the motivations and perceptions of individuals with a migrant background regarding their participation in mandatory conscript service in Finland. We employ Max Weber's theoretical framework on social action, which delineates four distinct archetypes: traditional, value-rational, instrumental-rational, and affective social actions. Our analysis draws from 36 interviews conducted with individuals with migrant backgrounds and analyses the meanings these individuals associate with their decision to engage or abstain from conscript service within the context of Finland's national defence system. We find that participation can be explained through a mix of overlapping social actions, and that none of Weber ́s categories alone sufficiently explain the motives to participate. The role of traditional social action in explaining the participation of individuals with a migrant background was particularly central as many considered military service as an important tradition of men in Finland uniting both peers and generations. For many, service also functioned as a means to an end, such as for example getting employed, thus serving an instrumental-rational purpose. Value-rational motives, on the other hand, were found to be particularly related to gender norms and nationalistic norms of performing military service being the proper action for men. Although emotions and affections also played a small role in the reasons for participation, their significance was found to be limited in explaining participation.